THE INFLUENCE OF SERVICE QUALITY AND PRICE TOWARD TRUST AND ITS IMPACT ON CUSTOMER LOYALTY OF LOW COST CARRIER INDONESIA - Rizan, Mohammad; Setyaningsih, Restu; Saidani, Basrah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This study was conducted to determine the descriptive and empirical impact of service quality and price on customer loyalty by the trust as a mediator variable. The object of this research was 200 respondents who have ever used the service of Indonesia AirAsia at least two times in Jakarta. Methods of data collection using survey methods. Data analysis using SPSS version 22 and SEM (Structural Equation Model) of a statistical package LISREL 8.7 to process and analyze the research data. The results of descriptive test explained that the service quality and price provided is good according to the customer, so that the customer is believe and tend to be a loyal customer of Indonesia AirAsia.The hypothesis test shows; (1) price has positive and significant effect on customer loyalty, but positive effect is insignificant on service quality to customer loyalty; (2) service quality and price has positive and significant effect on trust; (3) trust has positive and significant effect on customer loyalty; (4) service quality and price has positive and significant effect on customer loyalty through trust as mediating variable. Keywords: service quality, price, trust, customer loyalty